Penguatan Pesantren: Pencegahan Dan Mitigasi Risiko Kekerasan Seksual Di Pondok Pesantren Darul Ikhlas - Rita Defriza; Hamdanil Hamdanil (Abdimas Indonesian Journal, 2026)
Sexual violence in Islamic boarding schools is a serious problem that requires comprehensive prevention and risk reduction efforts. The purpose of this community service activity is to improve the ability of the Darul Ikhlas Islamic Boarding School to stop and deal with sexual violence through methods based on Islamic values. Participatory Action Research (PAR) is used as a method to carry out service activities. Participatory Action Research (PAR) involves mapping the risk of sexual violence, making prevention strategies based on Islamic principles, creating standard operating procedures (SOPs) to deal with sexual violence, and socialization and assistance to pesantren residents. The results of the activity showed that risk mapping revealed structural and cultural factors such as a culture of silence, unclear power relations, lack of knowledge about self-protection, and the absence of a standard handling mechanism. By referring to Islamic values such as amanah, "iffah, justice, and maqasid al-shari'ah," pesantren gain moral legitimacy to protect students. In addition, standard operating procedures (SOPs) provide clear and organized guidelines for handling cases of sexual violence. Increasing literacy and awareness of pesantren residents, improving institutional performance, changing perspectives on sexual violence, and empowering students as subjects of self-protection are the results of these activities. This activity shows that incorporating Islamic values into the institutional system can help create a safe, dignified, and just pesantren environment.